(untitled) (Research, Society and Development, 2021)
Previous results showed the ethyl acetate phase (SP-AcOEt), obtained from aerial parts of Solanum paludosum, relaxed the aorta isolated in the endothelium-dependent and -independent manner. The vasorelaxant effects of SP-AcOEt was not characterized on aorta rings endothelium-denuded, thus this work aimed to elucidate the mechanisms endothelium-independent vasorelaxation on rat isolated aorta. The aorta was isolated from Wistar rats and mounted in glass baths containing 6 mL of normal Krebs physiological solution with pH at 7.4. The preparation was maintained at 37ºC and bubbled continuously with a mixture of 95% O2 and 5% CO2. Aortic rings were maintained for 1 hour by a resting tension of 1g and next were contracted with phenylephrine after the sustained contraction ACh was added to access the integrity of the endothelium. SP-AcOEt relaxed pre-contracted aorta by KCl-30mM or -80mM in a similar manner, suggesting blockade CaV, but not channel-K+ participating. SP-AcOEt also inhibited the contraction induced by CaCl2 and relaxed pre-contracted aorta by (±)-BayK8644 (EC50 = 16.9±1.3 μg/mL), which confirms the involvement of L-type CaV blockade. SP-AcOEt presented vasorelaxation endothelium-independent that involves L-type CaV blockade.